The verse drama of Charles Williams : a thesis presented in partial fuflillment of the requirement for the degree of Master of Arts in English at Massey University - Ward, Marianna (Massey University, 1970)
This thesis will consider only the Later verse-drama of Charles williams, from Thomas Cranmer of Canterbury (1936). Abbreviations used are Cranmer for Thomas Cranmer of Canterbury. Chelmsford for Judgment ot Chelmsford, and Good Fortune for The Death of Good Fortune. The text used, to which unspecified page numbers belong, is Collected Plays (O.U.P. 1963). I would like to thank Mrs. A.M. Hadfield field for her prompt reply to enquiries about the plays, the librarians at Massey University, and Mr. R.A. Neale and Mr. John Dawick for their supervision and encouragement. [FROM PREFACE]
Keywords: Williams, Charles, 1886-1945; Criticism and interpretation